An Investigatory Project of Turmeric (Curcuma Longa Linn) Extract as an Alternative Wound Healing Cream: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Turmeric has a lot of uses in our kitchen, but because of its high concentration of an activechemical substance called curcumin, it's been used as a treatment for a variety of conditions.Curcumin, however, is said to be rich in anti-inflammatory, antioxidant, antimicrobial, and anti-cancer properties.The result of the study in terms of ingredients, procedural methodology, effectiveness, andpresentation is Acceptable as assessed by the chemist and dermatologists. It indicates thatthere is a significant difference between the assessment of the two groups of respondents. Interms of ingredients, the mean achieved by the chemist is 3.3725, while the dermatologistattained 2.975. The attained variance of the chemist engineer is 0.062769, while thedermatologist attained 0.070625. The T-critical value is 0.163336 with a degree of freedom of8. The T-computed value is -0.3975. Therefore, it accepts Ho.Based on the results of the study. The T-critical value is greater than the T-computed value,showing that there is a significant difference between the assessment of the two groups ofrespondents.
Keywords: Medicine